Teacher identity construction: narrative research on a foreign language teacher with no formal pedagogical background - Cabrera Bellido, Oswaldo (2015)
Teacher identity construction deals with the way teachers make sense of theirwork experience and acquire relevant knowledge about their job. Becoming a teacher means building up a certain kind of identity which aims at finding an individual sense of coherence, one which society demands. This study focuses on the narrative identity construction of a foreign language teacher without formal pedagogical background.Resources, practices and tensions involved in identity work deriving from non-institutionalizaed labor trajectories are analyzed. The study pigeonholes the kinds of discursive resources, ten positioning practices and three sources of tension underpinning one foreign language teacher identity construction.